Effects of different closures for thickness diffusivity - Eden, Carsten (author); Jochum, Markus (author); Danabasoglu, Gokhan (author) (Ocean Modelling, 2009)
The effects of spatial variations of the thickness diffusivity (K) appropriate to the parameterisation of [Gent, P.R. and McWilliams, J.C., 1990. Isopycnal mixing in ocean circulation models. J. Phys. Oceanogr., 20, 150-155.] are assessed in a coarse resolution global ocean general circulation model. Simulations using three closures yielding different lateral and/or vertical variations in K are compared with a simulation using a constant value. Although the effects of changing K are in general small and all simulations remain biased compared to observations, we find systematic local sensitivities of the simulated circulation on K. In particular, increasing K near the surface in the tropical ocean lifts the depth of the equatorial thermocline, the strength of the Antarctic Circumpolar Current decreases while the subpolar and subtropical gyre transports in the North Atlantic increase by increasing K locally. We also find that the lateral and vertical structure of K given by a recently proposed closure reduces the negative temperature biases in the western North Atlantic by adjusting the pathways of the Gulf Stream and the North Atlantic Current to a more realistic position.